2017
DOI: 10.3389/fncel.2017.00310
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Exerts Anti-Tumor Activity by Inducing Mitochondrion and Endoplasmic Reticulum Apoptosis and Autophagic Cell Death in Human Glioblastoma Cells

Abstract: Glioblastoma (GBM) is the most advanced and aggressive form of gliomas. Dihydroartemisinin (DHA) has been shown to exhibit anti-tumor activity in various cancer cells. However, the effect and molecular mechanisms underlying its anti-tumor activity in human GBM cells remain to be elucidated. Our results proved that DHA treatment significantly reduced cell viability in a dose- and time-dependent manner by CCK-8 assay. Further investigation identified that the cell viability was rescued by pretreatment either wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…In parallel, DHA induced the expression of several autophagy‐related genes, including ATG12, BNIP3, and ULK1, and lowered the expression of mTOR, which normally represses autophagy. These data are in agreement with the reported ability of DHA to induce both apoptosis and autophagy in cancer cells. More than that, our study unravels a novel pathway through which DHA elicits its toxic effect.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In parallel, DHA induced the expression of several autophagy‐related genes, including ATG12, BNIP3, and ULK1, and lowered the expression of mTOR, which normally represses autophagy. These data are in agreement with the reported ability of DHA to induce both apoptosis and autophagy in cancer cells. More than that, our study unravels a novel pathway through which DHA elicits its toxic effect.…”
Section: Discussionsupporting
confidence: 93%
“…21 On testing DHA on six CCA cell lines and on immortalized cholangiocytes, we found that DHA elicited toxicity preferentially toward CCA cells. The IC50 for DHA in the CCA cell lines tested was in the range of 53-61 μM, and the final concentration used to induce cell death was 50 μM, that is in the range of the concentration used in similar in vitro and in vivo studies performed in a variety of cancer types 43,44 including cholangiocarcinoma, 45 hepatocarcinoma, 45 pancreatic cancer, 46,47 lung cancer, 48 18,19,51 and autophagy 12,15,52 in cancer cells. More than that, our study unravels a novel pathway through which DHA elicits its toxic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…γ-TT was shown to concurrently trigger ER stress and autophagy in inducing apoptosis in breast cancer cells. 55,56 Here, we also observed that abrogation of apoptosis by the pancaspase inhibitor Z-VAD-FMK significantly, but not completely, reverted the cytotoxic effect of δ-TT on CRPC cells. 29 In line with these observations, both the ER stress and the autophagy pathways were reported to mediate the anti-cancer activity of several natural compounds.…”
Section: Discussionsupporting
confidence: 54%
“…It was found that autophagic cell death played an important role in anticancer drugs [20,21]. DHA could induce autophagy in some human cancer cell lines, including esophageal cancer cells [22][23][24], while the precise mechanisms of DHA on cancer cells were still limited. In the present study, we explored the role of autophagy in DHA treated Eca109 cells and the associated mechanisms were identified as well.…”
mentioning
confidence: 99%